Disruption of extended defects in solid oxide fuel cell anodes for methane oxidation - Ruiz-Morales, Juan Carlos; Canales-Vázquez, Jesús; Savaniu, Cristian; Marrero-López, David; Zhou, Wuzong; Irvine, John T. S. (Nature, 2006)
Ion out the defects The search for electrochemically active oxides for use in fuel cell anodes has concentrated on materials with low defect concentrations. This is because at high concentrations, interaction between defects can limit the device's performance, a problem that could exclude some technologically important materials from consideration. A new approach, based on the disruption of the extended defect structure in a lanthanum-doped strontium oxide, provides an alternative route to electrochemical efficiency. The new material achieves impressive device performance and has the potential to lead to more efficient energy extraction by fuel cells from fossil- and carbon-neutral fuels. Point defects largely govern the electrochemical properties of oxides: at low defect concentrations, conductivity increases with concentration; however, at higher concentrations, defect–defect interactions start to dominate 1 , 2 . Thus, in searching for electrochemically active materials for fuel cell anodes, high defect concentration is generally avoided. Here we describe an oxide anode formed from lanthanum-substituted strontium titanate (La-SrTiO 3 ) in which we control the oxygen stoichiometry in order to break down the extended defect intergrowth regions and create phases with considerable disordered oxygen defects. We substitute Ti in these phases with Ga and Mn to induce redox activity and allow more flexible coordination. The material demonstrates impressive fuel cell performance using wet hydrogen at 950 °C. It is also important for fuel cell technology to achieve efficient electrode operation with different hydrocarbon fuels 3 , 4 , although such fuels are more demanding than pure hydrogen. The best anode materials to date—Ni-YSZ (yttria-stabilized zirconia) cermets 5 —suffer some disadvantages related to low tolerance to sulphur 6 , carbon build-up when using hydrocarbon fuels 7 (though device modifications and lower temperature operation can avoid this 8 , 9 ) and volume instability on redox cycling. Our anode material is very active for methane oxidation at high temperatures, with open circuit voltages in excess of 1.2 V. The materials design concept that we use here could lead to devices that enable more-efficient energy extraction from fossil fuels and carbon-neutral fuels.